High night temperature disrupts the assimilate utilization and yield potential in soybean - Lekshmy V. Sankarapillai; Bikash Adhikari; Mohan K. Bista; Amrit Shrestha; Salliana R. Stetina; K. Raja Reddy; Raju Bheemanahalli (Plant Stress)
The increasing high nighttime temperatures (HNT) during cropping seasons significantly impact soybean yields, highlighting the need to prioritize HNT tolerance in breeding. This study quantified the response of seventeen soybean genotypes to HNT during both reproductive and vegetative stages, offering a promising opportunity to improve HNT tolerance in soybeans. A 4.8 °C increase in nighttime temperature during the reproductive stage significantly reduced daytime transpiration (17 %) and stomatal conductance (30 %), resulting in a 21 % decrease in photosynthesis (A). This led to a complex physiological shift, with a 29 % increase in nighttime respiration (Rd) during the reproductive stage and an 8 % increase during the vegetative stage. The reproductive stage was more vulnerable than the vegetative stage, substantially increasing assimilate use to production (Rd/A). These changes resulted in a 2.8 % reduction in seed yield for every 1 °C rise in nocturnal temperature above 23 °C. At the reproductive stage, Rd/A showed a strong negative correlation with seed yield, while the reduction in seed yield was positively correlated with reduced seed oil (r = 0.55; P < 0.05) under HNT. Genotypes tolerant to HNT during the reproductive stage maintained a low Rd/A with minimal to no change in seed yield compared to sensitive genotypes. Furthermore, our study revealed a unique hyperspectral signature, showing reduced reflectance, particularly in the water absorption spectral band associated with sensitive genotypes under HNT. Our findings pointed critical physiological checkpoints associated with higher yield and quality under HNT. These results also establish a foundation for developing new heat-proof soybeans for warmer environments.